Simulasi Proses Pendistribusian Minyak Tanah Studi Kasus: PT. Pertamina (Persero) Unit Pemasaran Iii Cabang Bandung - Trisnawarman, Dedi (Lembaga Penerbitan Universitas Esa Unggul, 2008)
The goal of this paper is to explain the design of the simulation process for the kerosene at PT. Pertamina (Persero) Unit Pemeasaran III Cabang Bandung. The methodology used in this research is to do some simulation procedure starting from problem formulation, data collection, model definition, validation, building application, running simulation and analysing the result from the simulation. The software used in the simulation is extend simulation 6.0. The result of this distributed from depo to the individu consumer and the industrial consumer. It is also possible to get the profit which is got by the depot. It can be assumed by the total of the distributed kerosene. The procentage of the assumption is 32% for the distribution to the individual consumer and 68% for the distribution to the industrial consumer.Keywords: Distribute, Extend, Kerosene